Effects of circuit and interval training on Vo₂max in adolescent basketball athletes: The moderating role of body mass index - Arsil Arsil; Muhammad Fakhrur Rozi; Ali Md Nadzalan; Sanjib Kumar Bhowmik; Firunika Intan Cahyani; Frizki Amra; Twinkle Duwarah; Rudyanto (CV. FOUNDAE, 2026)
Background: Aerobic capacity (VO₂max) is a critical determinant of basketball performance due to the sport’s intermittent high-intensity demands. Although circuit training and interval training are widely used to improve aerobic fitness, limited evidence exists regarding the role of Body Mass Index (BMI) in moderating training outcomes among adolescent basketball athletes. Aims: This study aimed to examine the effects of training method (circuit vs. interval) and BMI category on VO₂max in adolescent basketball athletes, as well as the interaction between these variables. Methods: A 2×2 factorial experimental design was employed involving 40 basketball athletes aged 15–18 years. Participants were allocated to four groups based on training method (interval or circuit) and BMI category (low or high). VO₂max was assessed using the Beep Test, while BMI was calculated from height and weight measurements. Data were analyzed using two-way ANOVA at a significance level of 0.05. Result: No significant difference was found between interval and circuit training in VO₂max outcomes (p = 0.362), indicating that both methods produced comparable aerobic adaptations. A significant difference was observed between BMI categories (p = 0.036), with athletes in the low-BMI group demonstrating higher VO₂max values than those in the high-BMI group. No significant interaction between training method and BMI category was found (p = 0.685). Conclusion: Both interval and circuit training effectively improved VO₂max in adolescent basketball athletes. Nevertheless, BMI significantly affected the magnitude of improvement, suggesting that maintaining an optimal BMI may support better aerobic adaptation in youth basketball training programs.